DESKRIPSI KEMAMPUAN BERPIKIR KOMBINATORIK MATEMATIS SISWA - Erni Widiyastuti; Suci Utami (AlphaMath : Journal of Mathematics Education, 2017)
This research aims to find out the description of Mathematic Combinatory Thiking Ability of the Students. This is a descriptive qualitative research. The subject of the research was the students of Grade XI.MIA-5 SMAN 5 Purwokerto. The technique of the data collection in this research was by test, interview and documentation. The result of the students’ mathematic combinatory thinking ability was grouped in 3, namely the high, middle, and low. Each group was taken 3 as the respodents. The result of the research showed that mathematic combinatory thinking ability of the high could understand the problem faced and started to find the possibility of answering the correct answer, find all possible answers correctly, and able to solve more than one combinatory problem in one single mechanism. The students’ mathematic combinatory thinking ability of the middle could understand the problem faced and started to find the possibility of answering the correct answer, find all possible answers correctly. Then, the students’ mathematic combinatory thinking ability of the low could only understand the problem faced and started to find the possibility of answering the correct answer. Keyword: Mathematic Combinatory Thinking Ability